DETERMINANT ACCEPTANCE OF INFORMATION SYSTEMS IN THE COOPERATIVE OF PALM OIL PRODUCERS, MUSI BANYUASIN DISTRICT - Rizka agi sawitri; Luk Luk Fuadah; Suhel - (JAF (Journal of Accounting and Finance), 2020)
Application of Information Technology in Cooperative business entities is deemed necessary to be implemented in Cooperatives, where the implementation of the use of Technology will provide many conveniences and advantages in developing the Cooperative business itself. There are still many cooperatives that do bookkeeping manually which results in wasted time and value of effectiveness and efficiency. The objective to be achieved in this study is to analyze the effect of perception on PU and PEU on attitude toward using, and the effect of the user's attitude (attitude toward using) effect on acceptance information Systems. This research uses a quantitative approach with the type of research is causal. The sampling technique uses nonprobability techniques through purposive sampling. The sample used was 164 cooperative employees with primary data sources through questionnaires. The analysis technique used is SEM-PLS. The results obtained in this study are the PU has significantly positive effect on ATU, PEU has significantly positive effect on ATU and ATU has significantly influence on the acceptance of information systems.